Penerapan Tax Review Sebagai Dasar Evaluasi Atas Pemenuhan Kewajiban Perpajakan PPh Badan dan PPN - Setiawan, I Kadek Agus; Setiawan, Putu Ery (E-Jurnal Akuntansi, 2018)
Taxes as a source of state revenues are used as a source of funds for governments for national development and measuring instruments to regulate government policies. Taxation or tax review is a measure of all company transactions to calculate the amount of tax payable and predict potential taxes that may arise under applicable tax laws and regulations. This research was conducted at PT. KBIC which is engaged in cargo of Tax Year 2015. The purpose of this study is to determine the effect of the implementation of tax review of corporate income tax and value added tax. The method used in this research is descriptive comparative. Comparing the results of tax reporting by the company with the calculation of Corporate Income Tax and Value Added Tax at PT. KBIC tax year 2015 from the researcher in accordance with the applicable tax provisions in Indonesia. Based on the results of the research, the tax review of the Corporate Income Tax has found differences in the fiscal reconciliation report on the Office of Travel and Phone Charge accounts. On the company's travel account, the company can not show the official report or notes in the assignment explaining the subject or purpose of the Overseas official's travel related to the company's principal activity that causes the difference of tax correction between the taxpayer and the researcher. Tax review conducted on Value Added Tax, the taxpayer has reported the fiscal reconciliation report correctly and there is no mistake. Keywords : Tax Review, Corporate Income Tax and Value Added Tax.